Analisis Determinan Perilaku Kerja Berinovasi - M. Natsir; Sangkala; Yunus, Muhammad (Sawala : Jurnal Administrasi Negara, 2023)
Knowledge collecting and donating can change old ideas about human resource management by providing new processes, disciplines and knowledge, resulting in organizational innovation, especially innovative work behavior. This study aims to examine the effect of knowledge collecting and donating on innovative work behavior. Quantitative methods are used to test knowledge collecting and donating on innovative work behavior. The research location is at Hasanuddin University, Makassar City. The population in this study were all employees at the Hasanuddin University Finance Bureau with status as state civil servants as many as 44 people. Withdrawal of the number of samples in this study using saturated sampling. Primary data collection by distributing questionnaires. The data analysis technique uses multiple linear regression analysis. The results showed that knowledge collecting and knowledge donating had a positive and significant effect both partially and simultaneously on innovative work behavior.